2018
DOI: 10.1136/oemed-2018-105094
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response in workers exposed to low-dose ionising radiation

Abstract: Our results indicate that chronic exposure to a low dose of IR in occupational settings induces DDR in exposed subjects and may be mutagenic in workers with family history of cancer, suggesting that periodic surveillance might be advisable, along with exposure monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…However, this finding can be supported by something known as “radiation hormesis model,” which assumes that adaptive/protective mechanisms can be stimulated over time by low-dose radiation and that they can prevent the occurrence of mutations in the cells (Vaiserman, 2010). Evidence of hormesis throughout defined low-dose IR ranges was previously described (Crump et al, 2012; Gaetani et al, 2018; Qian et al, 2016; Sahin et al, 2009; Sakly et al, 2012; Ündeǧer et al, 1999).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, this finding can be supported by something known as “radiation hormesis model,” which assumes that adaptive/protective mechanisms can be stimulated over time by low-dose radiation and that they can prevent the occurrence of mutations in the cells (Vaiserman, 2010). Evidence of hormesis throughout defined low-dose IR ranges was previously described (Crump et al, 2012; Gaetani et al, 2018; Qian et al, 2016; Sahin et al, 2009; Sakly et al, 2012; Ündeǧer et al, 1999).…”
Section: Discussionmentioning
confidence: 76%
“…Fortunately, the application of principles of radiological protection has decreased the levels of exposure to IR in these workers, and they are usually below the limit of 20 mSv/year (Dobrzyńska et al, 2014; International Commission on Radiological Protection, 2007). However, several studies have shown increased genetic damage, such as frequency of micronuclei, chromosomal aberrations, and DNA strand breaks, after chronic exposure to low doses of IR from diagnostic X-ray and nuclear medicine areas (Bouraoui et al, 2013; Cardoso et al, 2001; Dobrzyńska et al, 2014; Doukali et al, 2017a; Gaetani et al, 2018; Garaj-Vrhovac and Kopjar, 2003; Güerci et al, 2006; Kopjar and Garaj-Vrhovac, 2005; Kumar et al, 2015; Sari-Minodier et al, 2007; Wojewódzka et al, 1998; Zakeri and Hirobe, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nagle et al 421 reported that low-dose irradiation of high-density murine and human glandular stem cells represented a dose threshold for DNA damage repair activation, leading to lowdose hyperradiosensitivity. Gaetani et al 422 investigated the effects of low-dose IR on DNA damage in circulating cells of occupationally exposed workers; the results showed that among workers with low-dose IR exposure, DNA repair activity was increased, and moreover, workers with cancer cases in their family history showed significantly reduced 8oxoguanine glycosylase 1-dependent DNA repair activity compared with those workers without any family history of cancer. Although the effects of low-dose radiation on DNA have attracted increasing attention over the past decade, the molecular mechanisms, biomarkers, and possible clinical applicability require further investigation.…”
Section: Challenges For Ir-induced Signal Transduction and Targeted Therapymentioning
confidence: 99%
“…MN formation is considered a reliable biomarker of exposure to clastogenic and aneugenic agents, including IR (26)(27)(28). In addition to MN, other cytogenetic tests, including the comet assay (29)(30)(31)(32) and chromosome aberration assays (33)(34)(35)(36), have confirmed the association between genotoxicity and low-dose radiation exposure.…”
Section: Resultsmentioning
confidence: 99%